Calprotectin-mediated survival of Staphylococcus aureus in coculture with Pseudomonas aeruginosa occurs without nutrient metal sequestration - Wei H. Lee; Emily M. Zygiel; Celis H. Lee; Amanda G. Oglesby; Elizabeth M. Nolan (mBio)
ABSTRACT Pseudomonas aeruginosa and Staphylococcus aureus are bacterial pathogens of major clinical concern that cause polymicrobial infections in diverse patient populations. Human calprotectin (CP; S100A8/S100A9 heterooligomer, MRP8/MRP14 heterooligomer) is a host-defense protein that contributes to nutritional immunity by sequestering multiple nutrient metal ions including Mn(II), Fe(II), and Zn(II). Here, we examine the consequences of metal availability and CP treatment on cocultures of P. aeruginosa and S. aureus. We report that CP elicits Fe-starvation responses in both P. aeruginosa and S. aureus in coculture, including the upregulation of genes involved in Fe uptake by both organisms. Moreover, analyses of pseudomonal metabolites in coculture supernatants further demonstrate Fe-starvation responses, showing that CP treatment leads to increased siderophore levels and reduced phenazine levels. Consistent with prior studies, growth under conditions of Fe depletion accelerated P. aeruginosa killing of S. aureus in coculture, but treatment with CP promoted S. aureus survival. Treatment with CP site variants lacking functional transition-metal-binding sites and metalated CP also enhanced S. aureus survival in coculture with P. aeruginosa, revealing that this consequence of CP treatment is independent of its canonical metal-sequestering function. Thus, the protective effects of CP treatment during coculture appear to override the observed Fe-starvation effects that make P. aeruginosa more virulent toward S. aureus. This work highlights an unappreciated facet of how CP contributes to host–pathogen and pathogen–pathogen interactions that are relevant to human infectious disease.IMPORTANCEThe current working model that describes how the innate immune protein calprotectin (CP) protects the host against bacterial pathogens focuses on its capacity to sequester multiple essential metal nutrients in a process called nutritional immunity. Our study further explores this function by focusing on the effects of metal availability and CP treatment on the dynamics of Pseudomonas aeruginosa and Staphylococcus aureus grown in coculture. These two bacterial pathogens are of significant clinical concern and colocalize with CP at infection sites. This work reveals that CP modulates P. aeruginosa/S. aureus coculture dynamics in a manner that is independent of its ability to sequester nutrient metal ions. This surprising result is important because it demonstrates that CP has metal-independent function and thus contributes to the host–pathogen and pathogen–pathogen interactions in ways that are not accounted for in the current working model focused on metal sequestration.